Recognizing Actions in 3D using Action-Snippets and Activated Simplices - Wang, Chunyu; Flynn, John; Wang, Yizhou; Yuille, Alan L. (Conference on Artificial Intelligence (AAAI), 2016)
Pose-based action recognition in 3D is the task of recognizing an action (e.g., walking or running) from a sequence of 3D skeletal poses. This is challenging because of variations due to different ways of performing the same action and inaccuracies in the estimation of the skeletal poses. The training data is usually small and hence complex classiﬁers risk over-ﬁtting the data. We address this task by action-snippets which are short sequences of consecutive skeletal poses capturing the temporal relationships between poses in an action. We propose a novel representation for action-snippets, called activated simplices. Each activity is represented by a manifold which is approximated by an arrangement of activated simplices. A sequence(of action-snippets)isclassiﬁedbyselectingtheclosestmanifoldandoutputtingthecorresponding activity. This is a simple classiﬁer which helps avoid overﬁtting the data but which signiﬁcantly outperforms state-of the-art methods on standard benchmarks.